EFEKTIVITAS EKSTRAK DAUN KUMIS KUCING (Orthosiphon aristatus) TERHADAP PERTUMBUHAN Malassezia furfur SECARA IN VITRO - Rafi Thoriq Akbar (2023)
Pitiriasis versicolor is a type of dermatomycosis caused by the fungus Malassezia furfur, with the second-highest prevalence in Indonesia. Long-term use of chemical-based drugs can cause immune and side effects. Java tea leaves contain bioactive compounds such as alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, steroids, and glycosides, which are known to have a potency to inhibit fungal growth. The aim of this research is to determine the effectiveness of java tea (Orthosiphon aristatus) leaves extract in inhibiting the growth of the fungus M. furfur. This research is included in the pure experimental research conducted in vitro in the laboratory, with the type of research being a post-test group design only. The antifungal activity test used the well-diffusion method with independent variables in the form of extract concentrations of 1.25%, 2.5%, 5%, 10%, and 25%, the control variable consists a positive control of 2% ketoconazole and a negative control of DMSO solution, with the growth of M. furfur as the dependent variable. The statistical test used was the Kruskal-Wallis followed by the Mann-Whitney Post-Hoc test. Inhibition zone observations were carried out at 24 and 48 hours. The results showed that java tea leaves were effective in inhibiting the growth of M. furfur. The extract concentration that had the highest inhibiting effect was 10%, with an average inhibition zone diameter of 5.99 mm at 24 hours, creating a significant difference with other concentrations.